Automated Umbilical Cable Control System for Mobile Robot Navigation - Thiago Neto, Nilton S.; Torres, Mário César Delunardo; Cid, André Luiz Maciel; Peraira Junior, Renato Silva; Bespaloff, Yuri Maciel; Barros, Luiz Guilherme Dias de; Azpúrua, Héctor; Freitas, Gustavo (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XXI Simpósio Latino Americano de Robótica, 2024)
The deployment of mobile robots is becoming increasingly prevalent across a range of industrial and scientific domains. A crucial task of these robots is to perform inspections and monitoring in environments that pose significant risks to workers safety and health, such as confined spaces or areas with restricted accessibility. In these contexts, mobile robots are frequently operated remotely, requiring robust communication systems. One potential solution involves the utilization of an umbilical cable, which can also be used to rescue the robot in the event of a malfunction. Nevertheless, tethered robots present challenges, including friction-induced drag and the risk of the cable entangling with the robot’s locomotion system. This article proposes an automated mechanism designed to regulate the release and retraction of the umbilical cable, ensuring it remains taut and synchronized with the robot’s movements while estimating the distance traversed by the robot. The article presents the design and implementation of this automated system, alongside tests conducted with the EspeleoRobô in controlled laboratory settings and during field activities to inspect two railway culverts. The experiments indicate that the proposed system minimizes the number of personnel required for field operations and provides distance travelled by the robot, which can be used both as a reference for inspection attention points and to improve the robot’s localization and autonomous navigation system.